Design and optimize bone-like implants fabricated by EBM - Jiang, Yue (2017)
Additive manufacturing technology, also known as 3D printing technology, is a growing technology which has gathered worldwide researchers’ interests. Additive manufacturing enables replicating builds from computer-aided design (CAD) file into real 3D objects. The principle of additive manufacturing is initiating the builds from a starting plane and adding materials layer by layer. The materials used in additive manufacturing can be plastic, concrete and metal. This report focuses on using electron beam melting technology which is one of the additive manufacturing techniques, to design and optimize shaft-like (thigh bone) implants. AM technology has many advantages, including: increased design flexibility, improved end-product performance, reduced production time, lower manufacturing cost and material waste, and extended product life. Many researches studied on mesh structures and stochastic structures. However, seldom of the researches obtained the ideal mechanical properties suitable for human bone replacements. This report will study on new mesh structures that may fulfil the thighbone shaft implants requirements on compressive yield stress and Young's modulus.